ANALISA KELELAHAN KERJA PADA PEKERJA BAGIAN GUDANG DI PT. NOK FREUDENBERG SEALING TECHNOLOGIES BATAM - Samuel Nainggolan, Jonando; Zetli, Sri (LPPM Universitas Putera Batam, 2022)
Work fatigue is a common problem in the work area, but it is often ignored in the interest of the company's smooth production. Uncontrolled work fatigue can have a negative impact on workers both physically and psychologically. In this study, workers were given a workload of up to 35 kg hours, often they worked overtime for up to 12 hours per day, causing work fatigue. The purpose of this study was to determine the category of work fatigue and the factors that affect work fatigue of warehouse workers at PT Nok Fredeunberg Batam Batam. The method used in this study is a subjective self-assessment test method, which can be used to measure the subjective level of work fatigue of the workforce. The results of this study are the fatigue category of warehouse workers at PT Nok Fredeunberg Batam is in the high fatigue category, followed by the moderate fatigue category. Spearman correlation test results show that working hours (sig = 0.00), workload (sig = 0.00) affect work fatigue. In order to be able to advise warehouse workers to carry out their duties or workloads in accordance with their physical abilities and work abilities, it is expected that there will be a break. Then it is hoped that the leadership of PT Nok Fredeunberg Batam Batam can add mechanical equipment to lift and move goods and rotate working hours ideally.